Designing a Holistic Composite Metric for Sustainable Integrated Solid Waste Management: Economic, Social, and Environmental Perspectives - Oluwanimifise, Michael Kolawole; Anyaeche, Christopher Osita (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2026)
The Sustainable Development Goals (SDGs) have provided the opportunity to ensure adequate, safe, and affordable housing and basic services (including sustainable waste management) for all by 2030. A Sustainable Integrated Solid Waste Management System (SISWMS) is defined as one that fits a particular location with its inherent characteristics and peculiarities in line with the SDGs. There is no one-size-fits-all, comprehensive waste management system or metric that worked everywhere in the world indefinitely. Hence, waste management stakeholders worldwide were actively engaged in designing their own versions of the Sustainable Integrated Solid Waste Management Composite Index (SISWMCI) and frameworks that were economically, environmentally, and socially viable. This work aimed to develop a scalable, versatile, holistic, and innovative tool, in the form of a metric, to assess and benchmark solid waste management practices and systems. The proposed SISWMS framework and metric were rooted in the tripod of SDG pillars (economic, social, and environmental domains), interwoven using the Analytical Hierarchy Process (AHP) and Multi-Criteria Decision-Making (MCDM) weighting and aggregation methodologies, applied to 45 indicators across 10 sub-domains. The results indicated a red signal requiring urgent intervention, as the overall performance was 0.46, aggregated from the economic (0.49), social (0.49), and environmental (0.40) performance scores. The proposed metric was expected to serve as a robust and reliable sustainability performance benchmarking and improvement tool for waste management practices at the area, local government, state, and national levels.